2012
DOI: 10.3390/ijerph9062159
|View full text |Cite
|
Sign up to set email alerts
|

The US/Mexico Border: A Binational Approach to Framing Challenges and Constructing Solutions for Improving Farmworkers’ Lives

Abstract: Mexican migrant and seasonal farmworkers in the US-Mexico border region face health hazards and occupational risks and are becoming commonly known in the public health literature. According to several studies, farmworkers have high levels of chronic diseases such as diabetes and respiratory problems, are at risk for infectious diseases, and experience among the highest incidences of work-related injuries of any profession. The findings from two studies are considered and presented with the objective of contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
(8 reference statements)
0
17
0
1
Order By: Relevance
“…However, there are two sample characteristics that should be accounted for: (1) interviews were obtained from owners/managers identified by the association of producers (Fundación PRODUCE) and the governmental program that oversees the migrant farmworkers (PRONJAG, the National Program with Agricultural Laborers, under the Ministry of Social Development or SEDESOL) as those largest agribusiness in the region and (2) sample of interviewed agribusiness owners were table grape farm owners and vegetable farm owners, whose differences in living conditions of farmworkers are well documented (4) and are related to requirements of certification for good agricultural practices.…”
Section: Study Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are two sample characteristics that should be accounted for: (1) interviews were obtained from owners/managers identified by the association of producers (Fundación PRODUCE) and the governmental program that oversees the migrant farmworkers (PRONJAG, the National Program with Agricultural Laborers, under the Ministry of Social Development or SEDESOL) as those largest agribusiness in the region and (2) sample of interviewed agribusiness owners were table grape farm owners and vegetable farm owners, whose differences in living conditions of farmworkers are well documented (4) and are related to requirements of certification for good agricultural practices.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Families of migrant farmworkers experience higher poverty rates than the general population, thereby increasing the synergism between poor nutrition and a depressed immune system (3). This scenario and the living conditions of communities or agricultural fields, where they arrive, expose the individual to both infectious and chronic degenerative diseases (4). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that among a sample of 298 farmworkers in the southwest US, 21.5% and 16.1% reported having received a diagnosis of hypertension and diabetes, respectively. 33 Although providing a foundation for chronic disease concerns among the MSFW population, this study relied on self-reported data and did not stratify by migrancy status. To bridge this research gap, this current study was designed to explore CVD risk profiles in the MSFW population in the Midwest and to determine whether there are potential CVD risk differences by migrant or seasonal status.…”
Section: Introductionmentioning
confidence: 99%